Laser-emitting aqueous bioreactors for ultrasensitive bioactivity analysis - Guocheng Fang; Po-Hao Tseng; Jie Liao; Song Zhu; Tian Zhou; Hangrui Liu; Hui Zhu; Dayong Jin; Lan Yang; Yu-Cheng Chen (Proceedings of the National Academy of Sciences, 2025)
Water droplets, acting as natural bioreactors and optical whispering-gallery-mode (WGM) resonators, hold the potential for laser-assisted analysis. However, water/aqueous droplet lasers can only survive in air with a limited lifespan (<100 s) due to rapid evaporation, restricting their applications in bioreactions. To address this challenge, we introduce laser-emitting aqueous bioreactors (LEABs) in fluorocarbon oils. These LEABs enable stable laser emission and extend a droplet lifespan over 1,000-fold. LEABs enable the encapsulation of bioactive materials for long-term analysis with unique lasing characteristic fingerprints. The reactions within LEAB can interact with the most resonating light, enhancing detection sensitivity by over 100-fold compared to conventional WGM sensors. By integrating LEABs with microfluidic droplet technology, we demonstrated their application in monitoring enzyme activity and cellular metabolism at single-cell and multicellular levels. Furthermore, we showed the laser threshold-gated screening of single yeast. This platform can bridge the gap between laser technology and biochemical applications, broadening the scope of laser-based analysis.